Sistem Informasi Pendaftaran Pelatihan Calon Tenaga Kerja dan Tenaga Kerja Berbasis Web - Fajar, Mochamad; Lutvi Azizah, Nuril; Sumarno, Sumarno; Suprianto, Suprianto (Indonesian Journal of Applied Technology, 2024)
The Sidoarjo District Manpower Office has the task of assisting the Sidoarjo Regent in carrying out government affairs which fall under regional authority in the field of employment. The Sidoarjo District Manpower Office manages employment data which includes data on job seekers, companies, job vacancies and job training. This still needs special attention because current employment management is not well managed, job seekers in Sidoarjo Regency still have difficulty in choosing job vacancy information. In addition, the Sidoarjo Regency Manpower Office has difficulty in preparing training programs that are in accordance with the needs of the labor market because data processing is not yet online and integrated. This research was conducted with the aim of building an Employment Management Information System application at the Sidoarjo Regency Manpower Office. It is expected that the application built by the author is able to facilitate the Sidoarjo Regency Manpower Office in managing employment data and providing the best service to residents in Sidoarjo Regency. Keywords: Website, Information System, Sidoarjo Regency, Manpower Office.